Region of Interest (ROI) Determination System on SO-40F Pias Card’s Type for Measurement of Sunshine Duration (Case Study: St. Barongan) - Pujiastuti, Asih (SENATIK STT Adisutjipto, 2019)
The burn marks on the Pias Card are located on a scale of 6 -18 data is the sunshine duration. Determination of Region of Interest (RoI) is done with the aim of reducing noise in the Pias Card image segmentation process. solar irradiation system developed to determine areas that are considered important according to scale using the Cropping method. The system testing was carried out using 107 data of Pias Cards. Type Pias Card is SO-40F. Cropping principle is still manual, namely by setting the height of the image (Heigth), the left border (Left), and the right border (Right) in pixels. Based on testing, the best value settings are Heigth (H) = 5, Left (L) = 125, and Right (R) = 250 with a percentage of cropping success is 91.67%.